How is The Effectiveness of Ethnoscience-Based Modules in Science Learning in Indonesia?: A Systematic Literature Review - Lestari, Ina; Zulirfan, Zulirfan (Scientiae educatia, 2024)
This research aims to determine the effectiveness of ethnoscience-based science modules in Indonesia for junior high school students.  The research method used is a systematic literature review using digital libraries, namely Google Scholar, Scopus, Eric, and Garuda. In this research, several stages were carried out, such as literature search strategies, selection procedures, data extraction, and data analysis. So that the selected literature is relevant, the search uses the keywords "module, ethnoscience, science". Next, a screening was conducted to obtain scientific article publications from 2020 to 2024. Based on keywords, 1990 articles were selected based on exclusion and inclusion criteria, resulting in 21 relevant articles. The results of this research are that the development of ethnoscience-based modules mostly uses ADDIE and 4D models, and materials that are widely used in developing ethnoscience-based science modules are additive and additive materials. It can be seen that ethnoscience-based science modules are effective in improving 21st-century skills. That is it, the results of this research open up good opportunities for new researchers to study this topic further and serve as a reference for researchers and teachers.